A REVIEW ON MFIS EFFICIENCY & ITS IMPACT SCENARIO - A, Mansurali; R, Swamynathan (Journal of Contemporary Research in Management (JCRM), 2013)
Microfinance sector is the most promising market which records the highest growth rates globally since 2002, the growth rate of over 50 percent in a year which beats the communication industry. In India Microfinance institutions have emerged as an important stakeholder in the microfinance sector in lending to the poor. Today MFIs being operated efficiently to remain sustainable by extending their loans to Bottom of Pyramid & below Poverty line people, the deprived segment, the prime target of the microfinance industry under the concept of financial inclusion, even though it has been slowdown by the regulations and crisis (In Andhra Pradesh). Malegam committee report shows that between 2007 and 2010, the number of outstanding loan account serviced by MFIs is reported to have increased from 10.04 million to 26.7 million and outstanding loans from about Rs.3800 crores to Rs.18344 crores. The researchers/researches have empirically proven that MFI’s are efficient in nature and it has a significant impact on the societal & financial upliftment of individuals and groups (women).This paper presents a review overview of MFIs efficiency and its impact on double-bottom line. This review paper consolidates list of propositions that enables further researches in MFIs.